Impact of certolizumab pegol on patient-reported outcomes in rheumatoid arthritis and correlation with clinical measures of disease activity. Issue 1 (December 2015) - Pope, Janet; Bingham, Clifton; Fleischmann, Roy; Dougados, Maxime; Massarotti, Elena; Wollenhaupt, Jürgen; Duncan, Benjamin; Coteur, Geoffroy; Weinblatt, Michael
Abstract Introduction The effect of certolizumab pegol (CZP) on patient-reported outcomes (PROs) was investigated in 1063 patients with rheumatoid arthritis (RA) from the REALISTIC trial (double-blind, placebo-controlled to week 12, open-label to week 28; randomized 4:1 [CZP:placebo]). Correlations between PROs and RA signs and symptoms, and the relative efficacy of these measures, were examined. Methods Adults with RA and an inadequate response to at least one disease-modifying antirheumatic drug were enrolled. PROs assessed included physical function (using the Health Assessment Questionnaire-Disability Index), pain, fatigue, sleep disturbance, Patient Global Assessment of Disease Activity (PtGA), Routine Assessment of Patient Index Data 3 (RAPID3), and Rheumatoid Arthritis Disease Activity Index (RADAI). Results Early significant and clinically meaningful improvements in all PROs were observed to week 12 with CZP vs. placebo and were maintained to the end of the trial (week 28). At week 12, up to one-third more CZP patients showed improvements compared with placebo that were greater than or equal to the minimal clinically important difference (MCID) in fatigue, sleep problems, pain, PtGA, RADAI, and RAPID3. The changes in PROs were correlated with clinical measures of disease activity, including the Disease Activity Score in 28 joints using C-reactive protein as well as tender and swollen joint counts. Conclusions Rapid improvements in PROs were seen in patients with RA treated with CZP. The magnitude of improvement exceeded the MCID in multiple domains and demonstrated that CZP improves aspects of health-related quality of life that are meaningful to patients and superior to placebo. PROs provide information complementary to clinical outcomes in assessment of treatment benefits. Trial registration ClinicalTrials.gov identifier:NCT00717236 . Registered on 15 July 2008.